Factors associated with sports-related dental injuries among young athletes: a cross-sectional study in Miyagi prefecture - Shinobu Tsuchiya; Masahiro Tsuchiya; Haruki Momma; Takuya Sekiguchi; Kaoru Kuroki; Kenji Kanazawa; Takeyoshi Koseki; Kaoru Igarashi; Ryoichi Nagatomi; Yoshihiro Hagiwara (BMC, 2017)
Abstract Background Sports-related dental injuries, such as tooth fracture, loosening, and avulsion, are a major concern among young athletes because they directly impair oral function. Although the preventive efficacy of mouthguards has been well established, the prevalence of sports-related dental injuries remains high among young athletes. The aim of this study is to identify the variables contributing to the risk of sports-related dental injuries by conducting a survey on large population of young athletes in Miyagi prefecture. Methods A cross-sectional study was conducted with school-aged athletes (aged 6-15 years, n = 5735) using a self-reported questionnaire. The questionnaire examined general variables, including sex, age, and body mass index; sports-related variables, including sports-type, team level, activity schedule, break time, and verbal/physical abuse by coaches; and lifestyle variables related to free time, including screen-time and sleep duration. Their associations with sports-related dental injuries were examined using multivariate logistic regression models. Results The prevalence of sports-related dental injuries was 13.3% (763 of 5735 young athletes) and was higher in males (14.3%, 592 of 4132) than in females (10.7%, 171 of 1603; adjusted odds ratios [ORs] and 95% confidence intervals [CIs]: 1.48 [1.22-1.79], p < 0.001). After stratification according to sex, significant associations with the prevalence of sports-related dental injuries were evident for three variables-insufficient break time, verbal abuse, and physical punishment-in males (adjusted ORs [95% CI]: 1.35 [1.03-1.77], p = 0.032; 1.31 [1.05-1.62], p = 0.015; and 1.36 [1.06-1.75], p = 0.016, respectively) but not in females (adjusted ORs [95% CI]: 0.88 [0.53-1.47], p = 0.623; 1.29 [0.87-1.91], p = 0.206; and 0.97 [0.57-1.63], p = 0.894, respectively). Conclusions Although our results might be based on the individual athlete's self-perception to the sports-related variables, our results suggest that insufficient break time, verbal abuse, and physical punishment from coaches are positively associated with the prevalence of sports-related dental injuries in young male athletes.